Characterization of the count rate performance of modern gamma cameras. Issue 3 (27th February 2013) - Silosky, M.; Johnson, V.; Beasley, C.; Cheenu Kappadath, S.
Abstract : Purpose: : Evaluation of count rate performance (CRP) is an integral component of gamma camera quality assurance and system deadtime ( τ ) may be utilized for image correction in quantitative studies. This work characterizes the CRP of three modern gamma cameras and estimates τ using two established methods (decay and dual source) under a variety of experimental conditions. Methods: : For the decay method, uncollimated detectors were exposed to a Tc‐99m source of relatively high activity and count rates were sampled regularly over 48 h. Input count rate at each time point was based on the lowest observed count rate data point. The input count rate was plotted against the observed count rate and fit via least‐squares to the paralyzable detector model (PDM) to estimate τ (rates method). A novel expression for observed counts as a function of measurement time interval was derived, taking into account the PDM and the presence of background but making no assumption regarding input count rate. The observed counts were fit via least‐squares to this novel expression to estimate τ (counts method). Correlation and Bland‐Altman analyses were performed to assess agreement in estimates of τ between the rates and counts methods. The dependence of τ on energy window definition and incident energy spectrum were characterized. The dual source method was also used to estimate τ and its agreement with estimates from the decay method under identical conditions was also investigated. The dependences of τ on the total activity and the ratio of source activities were characterized. Results: : The observed CRP curves for each gamma camera agreed with the PDM at low count rates but deviated substantially from it at high count rates. The estimates of τ determined from the paralyzable portion of the CPR curve using the rates method and the counts method were found to be highly correlated ( r = 0.999) but with a small (∼6%) difference. No statistically significant difference was observed between the estimates of τ using the decay or dual source methods under identical experimental conditions ( p = 0.13). Estimates of τ increased as a power‐law function with decreasing ratio of counts in the photopeak to the total counts. Also, estimates of τ increased linearly as spectral effective energy decreased. No significant difference was observed between the dependences of τ on energy window definition or incident spectrum between the decay and dual source methods. Estimates of τ using the dual source method varied as a quadratic on the ratio of the single source to combined source activities and linearly with total activity. Conclusions: : The CRP curves for three modern gamma camera models have been characterized, demonstrating unexpected behavior that necessitates the determination of both τ and maximum count rate to fully characterize the CRP curve. τ was estimated under a variety of experimental conditions, based on which guidelines for the performance of CRP testing in a clinical setting have been proposed.